Computational analysis for wax detection in deepwater pipelines using nuclear techniques - Nalber Miranda Leite; Carlos Alberto Brayner de Oliveira Lira; Abel Gámez Rodriguez (Brazilian Journal of Radiation Sciences, 2023)
Wax deposition along the extensive oilfield pipelines is a problem that affects the flow assurance. To solve it, one must monitor the wax formation in its initial stage. In this light, nuclear techniques are an effective alternative solution, as they can detect characteristics of materials or substances in an indirect and non-invasive manner. The present work shows a computational model using the MCNP6 (Monte Carlo N-Particle 6) code and the gamma radiation transmission profiling technique to detect different wax thickness. This fact is directly related to the attenuation of the gamma radiation beam when crossing the wax thicknesses.